Arsenic in santa catarina soils Arsênio em solos de santa catarina - Machado M.R.* (2021)
© 2021, Institute for Environmental Research in Hydrographic Basins (IPABHi). All rights reserved.Arsenic (As) is one of the most harmful chemical elements known to man and to the environment, mainly due its high toxicity and wide distribution; the content of this element within the soils is a genuine concern, thus making it paramount to know its natural contents in a regional context. The present study aimed to determine the natural Arsenic content in the A horizon of 31 soil profiles from the state of Santa Catarina, Brazil, which is useful in determining reference values, monitoring, remediation of contaminated areas, legal regulation and Brazilian laws. Soil samples were prepared following the USPEA 3051A SW-846 method and were previously chemically reduced from As(V) to AS(III) by using the BCR method. The determination was performed in an Inductively Coupled Plasma-Optical Emission Spectrometry-Hydride Generation (ICP-OES-HG at cold vapor). Results obtained from the soil groups reveal the materials of basaltic origins as the ones with more As content while those of sediment origins had lesser content. Evaluated soil profiles fit into the following descending order regarding their As content: Latossolos, according to EMBRAPA (Oxisols according to Soil Taxonomy) > Nitossolo (Ultisols, Oxisols (Kandic), Alfisols) > Chernossolos (---) = Cambissolo (Inceptisols) = Argissolo (Ultisols) > Neossolos (Entisols).